Internet of Things (IoT) Platform Using Web Services-Based The Laravel Framework in Wind Turbines - Yunior, Yudhis Thiro Kabul (Universitas Dharma Wacana, 2025)
The increasing need for sustainable electrical energy has driven the development of various renewable energy sources, one of which is wind power plants (wind turbines). The development of the Internet of Things (IoT) is a solution for monitoring and managing wind power plants remotely, in real time so that it is more efficient and centralized. The integration method on the Internet of Things (IoT) platform is to build a sensor system installed on the wind turbine output so that it can send operational data in real time. The background of this study will design and implement a power monitoring system on a wind turbine using an Internet of Things-based web service platform. The development of an Internet of Things-based power monitoring system on web services will be built using the Laravel framework which will be integrated with the power output of the wind power plant. This platform is expected to simplify the process of monitoring, controlling, and analyzing wind turbine performance in real time, so that it can increase operational efficiency and support the development of sustainable renewable energy.